2022
DOI: 10.3389/fphys.2022.830059
|View full text |Cite
|
Sign up to set email alerts
|

Low Ambient Temperature Exposition Impairs the Accuracy of a Non-invasive Heat-Flux Thermometer

Abstract: BackgroundIndirect core body temperature (CBT) monitoring from skin sensors is gaining attention for in-field applications thanks to non-invasivity, portability, and easy probe positioning. Among skin sensors, heat-flux devices, such as the so-called Double Sensor (DS), have demonstrated reliability under various experimental and clinical conditions. Still, their accuracy at low ambient temperatures is unknown. In this randomized cross-over trial, we tested the effects of cold temperature exposition on DS perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…On top of the PPG sensor, the chest patch provides body temperature using the double sensor method ( Figure 1 ), in which body temperature is calculated from two temperature thermistors separated by an insulating disk with a known heat transfer coefficient. Various studies have suggested the reliability and validity of heat-flux approaches and double sensor technology under different environmental conditions, as well as in clinical conditions ( Sakuragi et al, 1993 ; Gunga et al, 2009 ; Kimberger et al, 2009 ; 2013 ; Teunissen et al, 2011 ; Xu et al, 2013 ; Mazgaoker et al, 2017 ; Mendt et al, 2017 ; Gómez-Romero et al, 2019 ; Janke et al, 2021 ; Masè et al, 2022 ). Integrating this sensor allows for the first time the collection of all five basic vital signs needed in clinical practice using a single wearable device.…”
Section: Methodsmentioning
confidence: 99%
“…On top of the PPG sensor, the chest patch provides body temperature using the double sensor method ( Figure 1 ), in which body temperature is calculated from two temperature thermistors separated by an insulating disk with a known heat transfer coefficient. Various studies have suggested the reliability and validity of heat-flux approaches and double sensor technology under different environmental conditions, as well as in clinical conditions ( Sakuragi et al, 1993 ; Gunga et al, 2009 ; Kimberger et al, 2009 ; 2013 ; Teunissen et al, 2011 ; Xu et al, 2013 ; Mazgaoker et al, 2017 ; Mendt et al, 2017 ; Gómez-Romero et al, 2019 ; Janke et al, 2021 ; Masè et al, 2022 ). Integrating this sensor allows for the first time the collection of all five basic vital signs needed in clinical practice using a single wearable device.…”
Section: Methodsmentioning
confidence: 99%
“…Current technologies for monitoring body temperature for wellness and fitness applications rely on the measurement of skin surface temperatures. While skin surface temperatures are easy to measure, the relationship between the skin’s surface and core body temperatures is not straightforward [ 7 , 8 ]. Converting a skin surface measurement to a core body temperature demands knowledge of the heat transfer processes between (1) the core body volume and the skin surface, and (2) the skin surface and the ambient surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…Converting a skin surface measurement to a core body temperature demands knowledge of the heat transfer processes between (1) the core body volume and the skin surface, and (2) the skin surface and the ambient surroundings. A variety of heat transfer models are available to account for surface-to-environment heat flux when coupled with the so-called double sensor experimental configuration, originally proposed by Gunga and co-workers [ 7 , 8 , 9 ]. A more sophisticated heat transfer model, recently proposed by Shan et al [ 10 ], accounts for the effects of blood perfusion within the tissue matrix.…”
Section: Introductionmentioning
confidence: 99%